Pers dan Bangkitnya Kesadaran Nasional Indonesia pada Awal Abad XX - Miftahul Habib F (ISTORIA: Jurnal Pendidikan dan Sejarah, 2017)
AbstractThis study aims to: (1) find out the initial development of the press in the Dutch East Indies, (2) find out the role of print capitalism in the distribution of national consciousness Indonesia, (3) find out the related of press and the rise of Indonesian national consciousness. This study was conducted using the historcal method as described by Kuntowijoyo. The result of the study showed that the development of the press is always related to the social and political conditions related to age. The press in the early twentieth century was influenced by the ethical policies which idealize the advanced of indigenous peoples. The development of press is supported by print capitalism. Print capitalism allowed the spread of Indonesian national consciousness. National consciousness first manifested itself in the spread of the discourse of advances among the educated natives as well as the spread of the use of the Malay language as the lingua franca in the East Indies. The relation between the press and the rise of Indonesian national consciousness is seen in Bintang Hindia and Medan Prijaji. Bintang Hindia is a newspaper that contains many advances discourse. A number of important ideas in this newspaper among others Kaoem Moeda and Bangsawan Fikiran. Both of these ideas provide a stimulus for the political consciousness of the educated natives. Meanwhile, Medan Prijaji is a newspaper to be more radical than Bintang Hindia. The article in Medan Prijaji contains many criticisms to the colonial government and provide legal assistance to the reader which needed.  Keywords: Press, National Consciousness, Indonesia